Leśmian wszędobylski. Recenzja książki Żanety Nalewajk "Leśmian międzynarodowy - relacje kontekstowe. Studia komparatystyczne", Universitas, Kraków 2015, 332 s. - Dubyk, Halyna (Colloquia Litteraria, 2018)
The book about Bolesław Leśmian by Żaneta Nalewajk Leśmian międzynarodowy, relacje kontekstowe. Studia komparatystyczne [The International Leśmian, Contextual Relationships. Comparative Analysis] is an interesting attempt to look at the poetry of Bolesław Leśmian from the contextual perspective, which so far has been never attempted by Leśmian scholars. A detailed analysis taking into account homologies and filiations has been carried out. A novel approach has also been introduced, when Leśmian’s between the wars poetry has been shown to have been influences by contemporary authors.